Improving The Economic Mechanisms Of State Regulation And Support Of Trade Services - Sattarova Nargiz Tokhirovna (International Journal on Integrated Education, 2022)
This article discusses the need for trade services to be treated as a distinct sector in the regulatory process, as well as the fact that trade activities, like other services, are governed by government regulations, which are an important tool for setting prices, increasing incomes, and providing social protection. The specific significance and relevance of trade services in the development of the service sector is significant, and the country's future development of this sector is linked to government regulation and assistance.